2010
DOI: 10.1021/es100128n
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Arsenic in Urine and Saliva of Children Playing on Playgrounds Constructed from Chromated Copper Arsenate-Treated Wood

Abstract: Children may be exposed to arsenic during contact with structures treated with chromated copper arsenate (CCA). A high frequency of hand-to-mouth activity may increase their risk of ingesting arsenic. Previous work showed that arsenic concentrations in the hand-wash samples of children playing on CCA playgrounds were four times higher than those playing on non-CCA playgrounds. It is not clear whether playing on CCA playgrounds results in elevated overall exposure to arsenic. The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Also, the time period of exposure captured by hair and nail measurements depends on the specific segments collected and analyzed. Other target tissues (e.g., urothelial cells) and buccal and saliva samples have also been suggested (Bartolotta et al 2011; Hernández-Zavala et al 2008; Lew et al 2010). Although these emerging biomarkers deserve additional attention, a more expanded knowledge of toxicokinetic data and information on correlations with existing biomarkers and intake doses is needed before they are adopted for use in research.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Also, the time period of exposure captured by hair and nail measurements depends on the specific segments collected and analyzed. Other target tissues (e.g., urothelial cells) and buccal and saliva samples have also been suggested (Bartolotta et al 2011; Hernández-Zavala et al 2008; Lew et al 2010). Although these emerging biomarkers deserve additional attention, a more expanded knowledge of toxicokinetic data and information on correlations with existing biomarkers and intake doses is needed before they are adopted for use in research.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Salivary glands have high blood flow, and chemicals and their metabolites in blood can be distributed in saliva through passive diffusion, active transport, and ultrafiltration [4245]. Our previous efforts showed that As III and its metabolites are present in saliva in populations who were chronically exposed to arsenic via drinking water or from chromated copper arsenate treated wood in playgrounds [2325]. No attention has been paid to arsenic speciation in human saliva in clinical settings, in which APL patients were acutely exposed to high doses of As III via intravenous infusion.…”
Section: Discussionmentioning
confidence: 99%
“…c Correlation of TAs between urine and saliva (r = 0.794, P < 0.01, n = 70) total arsenic concentration were: iAs85%, MMA7%, and DMA4%. Subsequently, Lew et al, [23] analyzed arsenic species in saliva collected from 61 children who played on chromated copper arsenate (CCA) and non-CCA playgrounds also found that iAs was the most excreted arsenic compound.…”
Section: Comparison Of the Proportion Of Arsenic Species And Methylatmentioning
confidence: 99%